Heterogeneous catalyst as well as preparation method and application thereof

By using SiO2 and Group IVB metal oxide composite oxide support and surface treatment technology, the Pd and Mo are supported, the problems of difficulty in separation and low availability of existing catalysts in the hydrogenation reaction are solved, and efficient hydrogenation and multi-dimensional The effect of the use.

CN119425673AActive Publication Date: 2025-02-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202310974769.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2025-02-14
Estimated Expiration
2043-08-03

AI Technical Summary

Technical Problem

In the hydrogenation reaction, existing heterogeneous catalysts have problems such as difficulty in separating the catalyst from the product, large particle size of active components, low availability, and poor multiple use effects.

Method used

Using a composite oxide support of SiO2 and Group IVB metal oxide, the surface treatment is carried out through an impregnation solution containing organic cationic quaternary ammonium salt. The Pd and its oxides and Mo and its oxides are loaded, and the cluster of active components is controlled to be no more than 5nm. , improve the hydrogenation activity and recovery of the catalyst.

Benefits of technology

The hydrogenation activity and stability of the catalyst are significantly improved, and efficient hydrogenation is achieved at lower temperatures and pressures, ensuring multiple uses of the catalyst and easy separation and recovery, and reducing preparation costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425673A_ABST
    Figure CN119425673A_ABST
Patent Text Reader

Abstract

The invention discloses a heterogeneous catalyst and a preparation method thereof, and hydrogenated butadiene-acrylonitrile rubber and a preparation method and application thereof. The heterogeneous catalyst comprises a composite oxide carrier of SiO2 and IVB group metal oxide, and an active component Pd and an oxide thereof loaded on the composite oxide carrier, and the IVB group metal oxide is TiO2 and / or ZrO2; the surface characteristic of the composite oxide carrier is that three characteristic peaks exist at the position of 620-710 cm <-1 > and three characteristic peaks exist at the position of 2850-2960 cm <-1 > in an infrared spectrum. According to the present invention, the heterogeneous catalyst and the homogeneous catalyst cooperate, the high-molecular polymer material is subjected to hydrogenation saturation at the low temperature and the low pressure, the prepared hydrogenated high-molecular polymer, especially the nitrile rubber product, has the high hydrogenation degree, and the heterogeneous catalyst can be used for many times so as to provide the good application prospect. The catalyst is easy to separate and recover.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a heterogeneous catalyst and a preparation method and application thereof. Background Art

[0002] Nitrile rubber (NBR) is a copolymer made of acrylonitrile and butadiene monomers. It has excellent oil resistance, high wear resistance, good heat resistance and strong adhesion. Its disadvantages are poor low temperature resistance, poor odor resistance, low insulation performance and low elasticity. It is widely used in the preparation of various oil-resistant rubber products in the fields of automobiles, aviation, petroleum, etc.

[0003] Hydrogenated nitrile rubber (HNBR) is a product produced by catalytic selective hydrogenation of unsaturated olefin segments on the hydrocarbon chain of nitrile rubber (NBR). Hydrogenated nitrile rubber has excellent characteristics such as good oil resistance, heat resistance, chemical corrosion resistance, odor resistance, high tear resistance and wear resistance.

[0004] At present, the main method for industrial production of HNBR is solution hydrogenation, which mainly includes homogeneous hydrogenation and heterogeneous hydrogenation. Homogeneous hydrogenation refers to the process in which the active components of the catalyst are dispersed in the polymer solution in molecular form and the polymer is catalytically hydrogenated under certain reaction conditions. However, a common disadvantage of homogeneous solution hydrogenation is that it is difficult to separate the catalyst from the product.

[0005] The heterogeneous catalytic reaction system uses a supported precious metal catalyst, but the preparation of the supported catalyst still relies on the traditional impregnation method, which results in a larger particle size of the active component, significantly reducing the number of active centers. In addition, due to the weak interaction between the active component and the carrier, the precious metal is easily separated and lost from the carrier surface after strong stirring, which reduces the availability of the catalyst and affects the performance of the hydrogenated product. Ruiong Company uses SiO2 as a carrier to load Pd metal for hydrogenation preparation of nitrile rubber. The hydrogenation degree is above 95% at one time, but the effect of multiple uses of the catalyst is poor, and the degree of hydrogenation is significantly reduced.

[0006] Therefore, it is necessary to develop a catalyst and related use method, which can ensure a high degree of hydrogenation, easy separation and recovery of the catalyst, and multiple uses of the heterogeneous catalyst. Summary of the invention

[0007] In view of the above problems existing in the prior art, the present invention provides a novel supported noble metal heterogeneous catalyst, wherein the surface characteristics of the composite oxide carrier are as follows: -1 There are three characteristic peaks at 2850-2960cm -1There are three characteristic peaks at , the composite oxide carrier can significantly improve the dispersion of the active components on the catalyst surface, control the active component atomic cluster to be no more than 5nm, thereby significantly improving the hydrogenation activity of the catalyst, and then adopting the heterogeneous catalyst of the present invention to cooperate with the homogeneous catalyst, not only ensure that the high molecular polymer material is hydrogenated saturated at a relatively low temperature and pressure, the obtained hydrogenated high molecular polymer (especially hydrogenated nitrile rubber) product has a higher degree of hydrogenation, and can also ensure the repeated use of the heterogeneous catalyst, and the catalyst is easily separated and recovered. More meaningfully, the loss of the noble metal active component is avoided, the recyclability of the catalyst is further improved, and the preparation cost is reduced.

[0008] The first aspect of the present invention provides a heterogeneous catalyst, comprising: a composite oxide carrier of SiO2 and a Group IVB metal oxide, and an active component Pd and its oxide supported on the composite oxide carrier, wherein the Group IVB metal oxide is TiO2 and / or ZrO2; the surface characteristics of the composite oxide carrier are infrared spectra at 620-710cm -1 There are three characteristic peaks at 2850-2960cm -1 In the present invention, the infrared spectrum measurement conditions adopt Nicolet iS50 infrared spectrometer, the sample preparation and scanning adopt attenuated total reflection mode, and the scanning range is 4000~400cm -1 , resolution 4cm -1 , scan times 32 times. For example Figure 1 As shown, the surface characteristics of the composite oxide carrier of the present invention are as follows: -1 There are three characteristic peaks at 2850-2960cm -1 There are three characteristic peaks.

[0009] According to some embodiments of the heterogeneous catalyst of the present invention, the composite oxide support is obtained by surface treating a composite support of SiO2 and Group IVB metal oxide using an impregnation solution containing an organic cationic quaternary ammonium salt.

[0010] According to some embodiments of the heterogeneous catalyst of the present invention, the organic cationic quaternary ammonium salt is a C6 or higher long-chain alkyl quaternary ammonium salt, more preferably, the organic cationic quaternary ammonium salt is selected from dimethyl dioctadecyl ammonium chloride, hexadecyl trimethyl ammonium chloride and C 12-14 -At least one of alkyl dimethyl ethyl benzyl ammonium chloride.

[0011] According to some embodiments of the heterogeneous catalyst of the present invention, based on the total weight of the composite oxide support, the content of the Group IVB metal oxide is 5 to 25 wt %, and the content of SiO 2 is 75 to 95 wt %.

[0012] According to some embodiments of the heterogeneous catalyst of the present invention, the content of Pd and its oxide in terms of Pd is 0.5 to 2 wt %, based on the total weight of the heterogeneous catalyst.

[0013] According to some embodiments of the heterogeneous catalyst of the present invention, the heterogeneous catalyst also includes Mo and its oxide loaded on the carrier. The inventors surprisingly found that the composite oxide carrier of SiO2 modified with molybdenum and IVB group metal oxide was impregnated with a soluble salt of Pd by impregnation method, and then dried and calcined to obtain Pd-Mo / TiO2-SiO2; the modified carrier surface has a stronger binding ability to Pd, and Pd is more evenly dispersed, which improves the hydrogenation activity of hydrogenated nitrile rubber, and the activity is still very high after repeated use.

[0014] According to some embodiments of the heterogeneous catalyst of the present invention, the content of Mo and its oxides calculated as Mo is 0.1-0.5 wt% based on the total weight of the heterogeneous catalyst, such as but not limited to 0.1-0.4 wt%, 0.1-0.3 wt%, 0.1-0.2 wt%, 0.2-0.5 wt%, 0.2-0.4 wt%, 0.2-0.3 wt%, 0.3-0.5 wt%, 0.3-0.4 wt%, 0.4-0.5 wt%, etc.

[0015] According to some embodiments of the heterogeneous catalyst of the present invention, the particle size of the heterogeneous catalyst is 5 to 30 μm. For example, but not limited to 5 to 25 μm, 5 to 20 μm, 5 to 15 μm, 5 to 10 μm, 10 to 30 μm, 10 to 25 μm, 10 to 20 μm, 10 to 15 μm, 15 to 30 μm, 15 to 25 μm, 15 to 20 μm, 20 to 30 μm, 20 to 25 μm, etc. In the present invention, the particle size of the catalyst is measured according to the NB / SH / T 0951-2017 test method, using a laser particle size analyzer of the MS2000 model produced by Malvern.

[0016] According to some embodiments of the heterogeneous catalyst of the present invention, the average pore size of the heterogeneous catalyst is 100-1200 nm. For example, but not limited to, 100-1000 nm, 100-800 nm, 100-600 nm, 100-500 nm, 100-400 nm, 100-300 nm, 100-200 nm, 200-1200 nm, 200-1000 nm, 200-800 nm, 200-600 nm, 200-500 nm, 200-400 nm, 200-300 nm, 300-1200 nm, 300-1000 nm, 300-800 nm, 300-600 nm, 300-500 nm, 300-400 nm, 400-120 0nm, 400~1000nm, 400~800nm, 400~600nm, 400~500nm, 500~1200nm, 500~1000nm, 500~800nm, 500~600nm, 600~1200nm, 600~1000nm, 600~800nm, 600~700nm, 700~1200nm, 700~1000nm, 700~800nm, 800~1200nm, 800~1000nm, 900~1200nm, 900~1000nm, 1000~1200nm and the like. In the present invention, the average pore size of the catalyst is measured according to the first part of the mercury intrusion method for determining the pore size distribution and porosity of solid materials by mercury intrusion and gas adsorption method in GBT 21650.1-2008, using the AutoPoreIV 9500 high-performance fully automatic mercury intrusion instrument of Micromeritics Instruments, USA.

[0017] According to some embodiments of the heterogeneous catalyst of the present invention, the specific surface area of ​​the heterogeneous catalyst is 30 to 200 m 2 / g. For example, but not limited to 30 to 150 m 2 / g, 30~120m 2 / g, 30~100m 2 / g, 30~80m 2 / g, 30~60m 2 / g, 30~50m 2 / g, 50~200m 2 / g, 50~150m 2 / g, 50~120m 2 / g, 50~100m 2 / g, 50~80m 2 / g, 50~60m 2 / g, 80~200m 2 / g, 80~150m 2 / g, 80~120m 2 / g, 80~100m 2 / g, 100~200m 2 / g, 100~150m 2 / g, 100~120m 2 / g, 120~200m 2 / g, 120~150m 2 In the present invention, the specific surface area of ​​the catalyst is measured according to the first part of the mercury intrusion method of GBT 21650.1-2008 for determining the pore size distribution and porosity of solid materials by mercury intrusion and gas adsorption method, using the AutoPoreIV 9500 high-performance fully automatic mercury intrusion instrument of Micromeritics Instruments, USA.

[0018] A second aspect of the present invention provides a method for preparing a heterogeneous catalyst, comprising the following steps:

[0019] (1) performing a first impregnation of a SiO2 microsphere carrier with a solution containing a Group IVB metal compound, followed by a first drying and a first calcination to obtain a composite carrier, wherein the Group IVB metal compound is a titanium-containing compound and / or a zirconium-containing compound;

[0020] (2) treating the surface of the composite support with an impregnation solution containing an organic cationic quaternary ammonium salt to obtain a composite oxide support;

[0021] (3) The composite oxide support is impregnated with a soluble salt of Pd for a second time, and then dried and calcined for a second time.

[0022] According to some embodiments of the method for preparing a heterogeneous catalyst according to the present invention, the impregnation solution containing an organic cationic quaternary ammonium salt comprises an organic cationic quaternary ammonium salt, a solvent, and an acid.

[0023] According to some embodiments of the method for preparing a heterogeneous catalyst according to the present invention, the organic cationic quaternary ammonium salt is a C6 or higher long-chain alkyl quaternary ammonium salt, more preferably selected from dimethyl dioctadecyl ammonium chloride, hexadecyl trimethyl ammonium chloride and C 12-14 -At least one of alkyl dimethyl ethyl benzyl ammonium chloride.

[0024] According to some embodiments of the method for preparing a heterogeneous catalyst according to the present invention, the solvent is selected from at least one of deionized water, methanol, ethanol, acetone, butanone, tetrahydrofuran, o-xylene and p-xylene.

[0025] According to some embodiments of the method for preparing a heterogeneous catalyst of the present invention, the acid is selected from at least one of hydrochloric acid, sulfuric acid, nitric acid and citric acid. More preferably, the concentration of the acid is 1 to 98.3 wt%.

[0026] According to some embodiments of the method for preparing a heterogeneous catalyst of the present invention, in the impregnation solution containing an organic cationic quaternary ammonium salt, the concentration of the quaternary ammonium salt solution is 0.1 to 10 wt %. More preferably, the weight ratio of the organic cationic quaternary ammonium salt, the solvent, and the acid is 1:10 to 19:1 to 3. For example, 1 mL of 37 wt % concentrated hydrochloric acid in the embodiment weighs 1.18 g.

[0027] According to some embodiments of the method for preparing a heterogeneous catalyst according to the present invention, the surface treatment is impregnation and drying. Preferably, the conditions for the impregnation include: a temperature of 20 to 60°C and a time of 0.5 to 8 hours; the conditions for the drying include: a temperature of 50 to 120°C and a time of 2 to 10 hours.

[0028] According to some embodiments of the method for preparing the heterogeneous catalyst of the present invention, the surface characteristics of the composite oxide after the quaternary ammonium salt treatment are as follows: -1 There are three characteristic peaks at 2850-2960cm -1 There are three characteristic peaks at the infrared spectra. The infrared spectra can be measured by using a nicolet iS50 infrared spectrometer. The sample preparation and scanning adopt the attenuated total reflection mode. The scanning range is 4000~400cm -1, Resolution 4cm -1 , scan times 32 times.

[0029] In the present invention, the SiO2 microsphere carrier can be simultaneously impregnated with a solution of a titanium compound and / or a zirconium compound, and then dried and calcined to obtain a composite oxide carrier of SiO2, TiO2 and / or ZrO2; the SiO2 microsphere carrier can also be first impregnated with a solution of a titanium compound, and then dried and calcined, and then impregnated with a solution of a zirconium compound, and then dried and calcined to obtain a composite oxide carrier of SiO2, TiO2 and / or ZrO2; the SiO2 microsphere carrier can also be first impregnated with a solution of a zirconium compound, and then dried and calcined, and then impregnated with a solution of a titanium compound, and then dried and calcined to obtain a composite oxide carrier of SiO2, TiO2 and / or ZrO2.

[0030] According to some embodiments of the method for preparing the heterogeneous catalyst of the present invention, after step (2) and before step (3), the preparation method further comprises: dissolving a soluble salt of molybdenum and impregnating the surface-treated composite oxide support to obtain a surface-treated composite oxide support modified by Mo. The inventors surprisingly found that the composite oxide support modified by molybdenum is combined with the soluble salt of Pd impregnated by impregnation, and the modified support surface has a stronger binding ability to Pd, and Pd is more evenly dispersed, thereby improving the hydrogenation activity of hydrogenated nitrile rubber, and the activity is still very high after multiple uses.

[0031] According to some embodiments of the method for preparing a heterogeneous catalyst according to the present invention, the soluble salt of Mo is selected from at least one of molybdenum trioxide, ammonium molybdate, and ammonium polymolybdate.

[0032] According to some embodiments of the method for preparing a heterogeneous catalyst according to the present invention, the molar ratio of the soluble salt of molybdenum to SiO2 is 1:1500-2000, wherein the soluble salt of molybdenum is calculated as molybdenum element and SiO2 is calculated as Si.

[0033] According to some embodiments of the method for preparing the heterogeneous catalyst of the present invention, the solution used for dissolution is selected from at least one of ammonia water, a dilute acid solution and an alkaline solution. In the present invention, the dilute acid solution and the alkaline solution are intended to dissolve the soluble salt of Mo, which will not be described in detail herein.

[0034] According to some embodiments of the method for preparing a heterogeneous catalyst according to the present invention, the particle size of the SiO2 microsphere carrier is 5 to 30 μm. For example, but not limited to 5 to 25 μm, 5 to 20 μm, 5 to 15 μm, 5 to 10 μm, 10 to 30 μm, 10 to 25 μm, 10 to 20 μm, 10 to 15 μm, 15 to 30 μm, 15 to 25 μm, 15 to 20 μm, 20 to 30 μm, 20 to 25 μm, etc. In the present invention, the particle size of the SiO2 microsphere carrier is measured according to the NB / SH / T 0951-2017 test method, using a laser particle size analyzer of the MS2000 model produced by Malvern.

[0035] According to some embodiments of the method for preparing a heterogeneous catalyst according to the present invention, the average pore size of the SiO2 microsphere carrier is 100 to 1200 nm. For example, but not limited to, 100 to 1000 nm, 100 to 800 nm, 100 to 600 nm, 100 to 500 nm, 100 to 400 nm, 100 to 300 nm, 100 to 200 nm, 200 to 1200 nm, 200 to 1000 nm, 200 to 800 nm, 200 to 600 nm, 200 to 500 nm, 200 to 400 nm, 200 to 300 nm, 300 to 1200 nm, 300 to 1000 nm, 300 to 800 nm, 300 to 600 nm, 300 to 500 nm, 300 to 400 nm, 400 to 1200 nm. 0nm, 400~1000nm, 400~800nm, 400~600nm, 400~500nm, 500~1200nm, 500~1000nm, 500~800nm, 500~600nm, 600~1200nm, 600~1000nm, 600~800nm, 600~700nm, 700~1200nm, 700~1000nm, 700~800nm, 800~1200nm, 800~1000nm, 900~1200nm, 900~1000nm, 1000~1200nm and the like. In the present invention, the average pore size of the SiO2 microsphere carrier is measured according to the first part of the mercury intrusion method for determining the pore size distribution and porosity of solid materials by mercury intrusion and gas adsorption method in GBT 21650.1-2008, using the high-performance fully automatic mercury intrusion instrument AutoPoreIV 9500 of Micromeritics Instruments, USA.

[0036] According to some embodiments of the method for preparing a supported catalyst of the present invention, the specific surface area of ​​the SiO2 microsphere carrier is 30 to 100 m 2 / g. For example, but not limited to 30 to 100 m 2 / g, 30~90m 2 / g, 30~80m 2 / g, 30~70m 2 / g, 30~60m 2 / g, 30~50m 2 / g, 30~40m 2 / g, 50~100m 2 / g,

[0037] 50~90m 2 / g, 50~80m 2 / g, 50~70m 2 / g, 50~60m 2 / g, 80~100m 2 / g, 80~90m 2 In the present invention, the specific surface area of ​​the SiO2 microsphere carrier is measured according to the first part of the mercury intrusion method for determining the pore size distribution and porosity of solid materials by mercury intrusion method and gas adsorption method in GBT 21650.1-2008, and is measured by using the high-performance fully automatic mercury intrusion instrument AutoPoreIV9500 of Micromeritics Instruments, USA.

[0038] In the present invention, the silica microsphere carrier can be obtained by commercial purchase or homemade.

[0039] According to some embodiments of the method for preparing a heterogeneous catalyst of the present invention, the titanium-containing compound is selected from at least one of titanium sulfate, metatitanic acid, titanium tetrachloride and tetrabutyl titanate. For example, metatitanic acid can be dissolved in a dilute sulfuric acid solution. For another example, tetrabutyl titanate can be dissolved in an ethanol solution.

[0040] According to some embodiments of the method for preparing a heterogeneous catalyst according to the present invention, the zirconium-containing compound is selected from at least one of zirconium tetrachloride, zirconium sulfate, zirconium nitrate, zirconium oxychloride and zirconium oxalate.

[0041] According to some embodiments of the method for preparing a heterogeneous catalyst according to the present invention, the soluble salt of Pd is selected from sulfates, nitrates and halides of palladium, preferably at least one of palladium chloride, palladium nitrate, palladium acetate and palladium sulfate.

[0042] According to some embodiments of the method for preparing a heterogeneous catalyst according to the present invention, the weight ratio of the SiO2 microsphere carrier to the titanium-containing compound and / or the zirconium-containing compound is 7 to 20:1.

[0043] According to some embodiments of the method for preparing a heterogeneous catalyst of the present invention, the molar ratio of the composite oxide support to the soluble salt of Pd is 1:150-700.

[0044] According to some embodiments of the method for preparing a heterogeneous catalyst of the present invention, the conditions for the first impregnation include: a temperature of 20 to 60° C. and a time of 0.5 to 8 h.

[0045] According to some embodiments of the method for preparing a heterogeneous catalyst of the present invention, the conditions for the second impregnation include: a temperature of 20 to 60° C. and a time of 0.5 to 8 h.

[0046] According to some embodiments of the method for preparing a heterogeneous catalyst of the present invention, the first drying conditions include: a temperature of 105 to 130° C. and a time of 2 to 8 hours.

[0047] According to some embodiments of the method for preparing a heterogeneous catalyst of the present invention, the second drying conditions include: a temperature of 105 to 1830° C. and a time of 2 to 8 hours.

[0048] According to some embodiments of the method for preparing a heterogeneous catalyst of the present invention, the conditions for the first calcination include: a temperature of 450 to 650° C. and a time of 3 to 8 hours.

[0049] According to some embodiments of the method for preparing a heterogeneous catalyst of the present invention, the conditions for the second calcination include: a temperature of 450 to 650° C. and a time of 3 to 8 hours.

[0050] According to some embodiments of the method for preparing a heterogeneous catalyst according to the present invention, the amounts of the SiO2 microsphere carrier and the solution of the titanium compound are such that, based on the total weight of the prepared composite oxide carrier of SiO2 and TiO2 and / or ZrO2, the content of TiO2 and / or ZrO2 is 5 to 25 wt%, and the content of SiO2 is 75 to 95 wt%.

[0051] According to some embodiments of the method for preparing a heterogeneous catalyst according to the present invention, the amount of the soluble salt of Pd for the second impregnation of the composite oxide carrier of SiO2, TiO2 and / or ZrO2 satisfies that the content of Pd and its oxide is 0.5 to 2 wt% based on the total weight of the supported catalyst.

[0052] The third aspect of the present invention provides a heterogeneous catalyst obtained according to the above preparation method. It comprises: a composite oxide carrier of SiO2 and Group IVB metal oxide, and an active component Pd and its oxide loaded on the composite oxide carrier, wherein the Group IVB metal oxide is TiO2 and / or ZrO2; the surface characteristics of the composite oxide carrier are infrared spectrum at 620-710cm -1 There are three characteristic peaks at 2850-2960cm -1 In the present invention, the infrared spectrum measurement conditions adopt Nicolet iS50 infrared spectrometer, the sample preparation and scanning adopt attenuated total reflection mode, and the scanning range is 4000~400cm -1 , resolution 4cm -1 , scan times 32 times. For example Figure 1 As shown, the surface characteristics of the composite oxide carrier of the present invention are as follows: -1 There are three characteristic peaks at 2850-2960cm -1 There are three characteristic peaks.

[0053] According to some embodiments of the heterogeneous catalyst of the present invention, the composite oxide support is obtained by surface treating the composite support with an impregnation solution containing an organic cationic quaternary ammonium salt.

[0054] According to some embodiments of the heterogeneous catalyst of the present invention, the organic cationic quaternary ammonium salt is a C6 or higher long-chain alkyl quaternary ammonium salt, more preferably, the organic cationic quaternary ammonium salt is selected from dimethyl dioctadecyl ammonium chloride, hexadecyl trimethyl ammonium chloride and C 12-14 -At least one of alkyl dimethyl ethyl benzyl ammonium chloride.

[0055] According to some embodiments of the heterogeneous catalyst of the present invention, based on the total weight of the composite oxide support, the content of the Group IVB metal oxide is 5 to 25 wt %, and the content of SiO 2 is 75 to 95 wt %.

[0056] According to some embodiments of the heterogeneous catalyst of the present invention, the content of Pd and its oxide in terms of Pd is 0.5 to 2 wt %, based on the total weight of the heterogeneous catalyst.

[0057] According to some embodiments of the heterogeneous catalyst of the present invention, the heterogeneous catalyst also includes Mo and its oxide loaded on the carrier. The inventors surprisingly found that the composite oxide carrier of SiO2 modified with molybdenum and IVB group metal oxide was impregnated with a soluble salt of Pd by impregnation method, and then dried and calcined to obtain Pd-Mo / TiO2-SiO2; the modified carrier surface has a stronger binding ability to Pd, and Pd is more evenly dispersed, which improves the hydrogenation activity of hydrogenated nitrile rubber, and the activity is still very high after repeated use.

[0058] According to some embodiments of the heterogeneous catalyst of the present invention, the content of Mo and its oxides calculated as Mo is 0.1-0.5 wt% based on the total weight of the heterogeneous catalyst, such as but not limited to 0.1-0.4 wt%, 0.1-0.3 wt%, 0.1-0.2 wt%, 0.2-0.5 wt%, 0.2-0.4 wt%, 0.2-0.3 wt%, 0.3-0.5 wt%, 0.3-0.4 wt%, 0.4-0.5 wt%, etc.

[0059] According to some embodiments of the heterogeneous catalyst of the present invention, the particle size of the heterogeneous catalyst is 5 to 30 μm. For example, but not limited to 5 to 25 μm, 5 to 20 μm, 5 to 15 μm, 5 to 10 μm, 10 to 30 μm, 10 to 25 μm, 10 to 20 μm, 10 to 15 μm, 15 to 30 μm, 15 to 25 μm, 15 to 20 μm, 20 to 30 μm, 20 to 25 μm, etc. In the present invention, the particle size of the catalyst is measured according to the NB / SH / T 0951-2017 test method, using a laser particle size analyzer of the MS2000 model produced by Malvern.

[0060] According to some embodiments of the heterogeneous catalyst of the present invention, the average pore size of the heterogeneous catalyst is 100-1200 nm. For example, but not limited to, 100-1000 nm, 100-800 nm, 100-600 nm, 100-500 nm, 100-400 nm, 100-300 nm, 100-200 nm, 200-1200 nm, 200-1000 nm, 200-800 nm, 200-600 nm, 200-500 nm, 200-400 nm, 200-300 nm, 300-1200 nm, 300-1000 nm, 300-800 nm, 300-600 nm, 300-500 nm, 300-400 nm, 400-120 0nm, 400~1000nm, 400~800nm, 400~600nm, 400~500nm, 500~1200nm, 500~1000nm, 500~800nm, 500~600nm, 600~1200nm, 600~1000nm, 600~800nm, 600~700nm, 700~1200nm, 700~1000nm, 700~800nm, 800~1200nm, 800~1000nm, 900~1200nm, 900~1000nm, 1000~1200nm and the like. In the present invention, the average pore size of the catalyst is measured according to the first part of the mercury intrusion method for determining the pore size distribution and porosity of solid materials by mercury intrusion and gas adsorption method in GBT 21650.1-2008, using the AutoPoreIV 9500 high-performance fully automatic mercury intrusion instrument of Micromeritics Instruments, USA.

[0061] According to some embodiments of the heterogeneous catalyst of the present invention, the specific surface area of ​​the heterogeneous catalyst is 30 to 200 m 2 / g. For example, but not limited to 30 to 150 m 2 / g, 30~120m 2 / g, 30~100m 2 / g, 30~80m 2 / g, 30~60m 2 / g, 30~50m 2 / g, 50~200m 2 / g, 50~150m 2 / g, 50~120m 2 / g, 50~100m 2 / g, 50~80m 2 / g, 50~60m 2 / g, 80~200m 2 / g, 80~150m 2 / g, 80~120m 2 / g, 80~100m 2 / g, 100~200m 2 / g, 100~150m 2 / g, 100~120m 2 / g, 120~200m 2 / g, 120~150m 2 In the present invention, the specific surface area of ​​the catalyst is measured according to the first part of the mercury intrusion method of GBT 21650.1-2008 for determining the pore size distribution and porosity of solid materials by mercury intrusion and gas adsorption method, using the AutoPoreIV 9500 high-performance fully automatic mercury intrusion instrument of Micromeritics Instruments, USA.

[0062] The fourth aspect of the present invention provides a catalyst composition, comprising a homogeneous catalyst and the above-mentioned supported catalyst.

[0063] According to some embodiments of the catalyst composition of the present invention, homogeneous catalysts commonly used in the art can be used, such as transition metal ruthenium carbene complexes, Grubbs catalysts (such as catalysts for olefin metathesis), triphenylphosphine and triphenylphosphine chlorides of platinum group metals. Preferably, the homogeneous catalyst includes triphenylphosphine and triphenylphosphine chlorides of platinum group metals.

[0064] Specific transition metal ruthenium carbene complex catalysts include but are not limited to the following structures of formula (1) to formula (7):

[0065]

[0066]

[0067] The structure of the Grubbs catalyst includes but is not limited to that shown in formula (8):

[0068]

[0069] According to some embodiments of the hydrogenation method of hydrogenated nitrile rubber of the present invention, the triphenylphosphine chloride of a platinum group metal is triphenylphosphine rhodium chloride and / or triphenylphosphine ruthenium chloride.

[0070] According to some embodiments of the hydrogenation method of hydrogenated nitrile rubber of the present invention, the weight ratio of triphenylphosphine to triphenylphosphine chloride of platinum group metal is 2 to 5: 1. For example, but not limited to, 2 to 5: 1, 2 to 4: 1, 2 to 3: 1, etc.

[0071] According to some embodiments of the hydrogenation method of hydrogenated nitrile rubber of the present invention, the weight ratio of the supported catalyst to the homogeneous catalyst is 1:0.01-0.3, such as but not limited to 1:0.05-0.3, 1:0.1-0.3, 1:0.15-0.3, 1:0.16-0.3, etc.

[0072] The fifth aspect of the present invention provides a hydrogenation method for a hydrogenated high molecular polymer, comprising: dissolving the high molecular polymer in an organic solvent, and then adding the above catalyst composition to react.

[0073] According to some embodiments of the method for preparing hydrogenated nitrile rubber of the present invention, the high molecular polymer is nitrile rubber. In the art, nitrile rubber refers to a copolymer formed by polymerization of acrylonitrile and butadiene monomers, which will not be described in detail here.

[0074] According to some embodiments of the method for preparing hydrogenated nitrile rubber of the present invention, the organic solvent is selected from at least one of chlorobenzene, acetone, butanone, tetrahydrofuran, dichloromethane, chloroform, cyclohexanone, ethyl acetate and dimethylformamide.

[0075] According to some embodiments of the method for preparing hydrogenated nitrile rubber of the present invention, the amount of the heterogeneous catalyst is 5 to 20 wt % of the high molecular weight polymer.

[0076] According to some embodiments of the method for preparing hydrogenated nitrile rubber of the present invention, the reaction conditions include: temperature of 30 to 90° C., hydrogen pressure of 5 to 10 MPa, and reaction time of 5 to 10 h.

[0077] According to some embodiments of the preparation method of hydrogenated nitrile rubber of the present invention, the amount of organic solvent used to dissolve the high molecular weight polymer satisfies the content of the high molecular weight polymer of 0.1-10wt%, such as 0.1-10wt%, 0.1-8wt%, 0.1-6wt%, 0.1-4wt%, 0.1-2wt%, 0.1-1wt%, 0.5-10wt%, 0.5-8wt%, 0.5-6wt%, 0.5-4wt%, 0.5-2wt%, 0.5-1wt%, 1-10wt%, 1-8wt%, 1-6wt%, 1-4wt%, 1-2wt%, 3-10wt%, 3-8wt%, 3-6wt%, 3-4wt%, 5-10wt%, 5-8wt%, 5-6wt%, 7-10wt%, 7-8wt%, 8-10wt%, 9-10wt%, etc.

[0078] According to some embodiments of the method for preparing hydrogenated nitrile rubber of the present invention, the method for preparing hydrogenated nitrile rubber may further include: after the reaction is completed, recovering the heterogeneous catalyst by filtration or centrifugal separation, and recovering the homogeneous catalyst by ion exchange with ion exchange resin.

[0079] The sixth aspect of the present invention provides a hydrogenated high molecular polymer obtained according to the above-mentioned preparation method. Preferably, the hydrogenated high molecular polymer is hydrogenated nitrile rubber.

[0080] The seventh aspect of the present invention provides the above-mentioned heterogeneous catalyst, the above-mentioned preparation method, the above-mentioned catalyst composition, the above-mentioned hydrogenation method of the hydrogenated polymer or the application of the above-mentioned hydrogenated polymer in rubber products, especially in the field of hydrogenated nitrile rubber products.

[0081] Beneficial effects of the present invention:

[0082] (1) Using an impregnation solution containing an organic cationic quaternary ammonium salt to modify the composite oxide carrier of SiO2 and Group IVB metal oxide can significantly improve the dispersion of active components on the catalyst surface and control the atomic clusters of active components to be no larger than 5nm, thereby significantly improving the hydrogenation activity of the catalyst.

[0083] (2) The supported catalyst prepared based on SiO2 composite oxide has a pore structure suitable for the hydrogenation of macromolecules such as nitrile rubber. The TiO2 and / or ZrO2 on the surface of the carrier can improve the hydrogenation activity of the catalyst. The catalyst has good hydrogenation activity and stability.

[0084] (3) The heterogeneous catalyst of the present invention is coordinated with the homogeneous catalyst to achieve hydrogenation saturation of the polymer material at a relatively low temperature and pressure, and the obtained hydrogenated polymer (especially hydrogenated nitrile rubber product) has a relatively high degree of hydrogenation.

[0085] (4) After the reaction is completed, the heterogeneous catalyst is recovered by filtration or centrifugal separation, and the homogeneous catalyst is recovered by ion exchange with an ion exchange resin. This can also ensure that the heterogeneous catalyst can be used multiple times and the catalyst is easy to separate and recover.

[0086] (5) The heterogeneous catalyst and the method for preparing hydrogenated nitrile rubber of the present invention are used. In a preferred case, precious metal palladium is used as the active component to prepare the immobilized nitrile rubber heterogeneous catalyst, which further improves the recyclability of the catalyst and significantly reduces the cost of the catalyst, thereby reducing the production cost of the hydrogenated high molecular polymer (especially the hydrogenated nitrile rubber product). BRIEF DESCRIPTION OF THE DRAWINGS

[0087] Figure 1 This is the infrared spectrum of the composite oxide support provided in Example 1 of the present invention.

[0088] Figure 2 This is a graph showing the TEM characterization results of the heterogeneous catalyst A provided in Example 10 of the present invention.

[0089] Figure 3 This is the infrared spectrum of the TiO2-SiO2 composite carrier without surface treatment in test comparative example 1.

[0090] Figure 4 This is the infrared spectrum of the surface-treated SiO2 carrier of test comparative example 5.

[0091] Figure 5 Comparison chart of infrared spectra of carriers of Example 1, Test Comparative Example 1 and Test Comparative Example 5. DETAILED DESCRIPTION

[0092] In order to make the present invention more easily understood, the present invention will be described in detail below in conjunction with embodiments. These embodiments are only for illustration and are not intended to limit the application scope of the present invention.

[0093] In the following examples and comparative examples,

[0094] (1) SiO2 microsphere carrier was purchased from Shandong Bangkai Materials Co., Ltd.

[0095] (2) Dimethyldioctadecylammonium chloride, purchased from Beijing Bailingwei Technology Co., Ltd., CAS No. 61789-80-8.

[0096] (3) Hexadecyltrimethylammonium chloride, purchased from Beijing Bailingwei Technology Co., Ltd., CAS No. 112-02-7.

[0097] (4)C 12-14-Alkyl dimethyl ethyl benzyl ammonium chloride was purchased from Beijing Bailingwei Technology Co., Ltd. with a CAS number of 85409-23-0.

[0098] (5) In the present invention, the content of Cu and its oxides expressed as Cu is obtained by ICP atomic emission spectrometry analysis.

[0099] (6) TiO2 content was measured using a spectrophotometer. The principle used is: in sulfuric acid solution, Ti 4+ It forms a yellow complex with hydrogen peroxide. Titanium dioxide forms titanium sulfate in hot sulfuric acid, and titanium sulfate reacts with hydrogen peroxide to form a stable orange-yellow [TiO(H2O2)] 2- , measured by spectrophotometer at 430nm.

[0100] (7) Similarly, the ZrO2 content was determined using a spectrophotometer.

[0101] (8) Infrared spectra were measured using a Nicolet iS50 infrared spectrometer. Sample preparation and scanning were performed using the attenuated total reflection mode. The scanning range was 4000–400 cm -1 , resolution 4cm -1 , scan times 32 times.

[0102] (9) TEM characterization conditions: The catalyst was observed using a high-resolution transmission electron microscope (Jem-3010) with an acceleration voltage of 200 KV for HR-TEM characterization. The samples were fully ground into powder before testing. A small amount of the sample was added to anhydrous ethanol and placed in an ultrasonic cleaning machine (model PS-10, Shenzhen Jiekang Ultrasonic Cleaning Machine Co., Ltd.) for ultrasonic separation for 15 to 20 minutes. Finally, the suspension was continuously dripped onto the microgrid using a dropper and allowed to dry naturally.

[0103] (10) The particle size of the atomic cluster of the active component copper was characterized by transmission electron microscopy (TEM) and measured according to the scale.

[0104] [Example 1]

[0105] 85 g of SiO2 microsphere carrier (particle size of 20 μm, average pore size of 110 nm) was impregnated with 420 mL of a solution of titanium sulfate with a concentration of 0.45 mol / L at 25°C for 6 h, and the precipitate was dried at 110°C for 6 h and calcined at 550°C for 5 h. A TiO2-SiO2 composite carrier (SiO2 content of 85 wt%) with a TiO2 content of 15 wt% was obtained.

[0106] Take 5g of dimethyldioctadecylammonium chloride, add 95g of o-xylene, mix evenly with 10mL of hydrochloric acid (mass fraction 37wt%), prepare an impregnation solution, use the above impregnation solution to impregnate the TiO2-SiO2 composite carrier at room temperature, impregnate for 2h, and then dry at 60℃ for 12h to obtain a TiO2-SiO2 composite oxide carrier.

[0107] The prepared composite oxide support was characterized by infrared spectroscopy. Figure 1 As shown, the infrared spectrum of the SiO2-TiO2 composite oxide after surface treatment. It can be seen from the infrared spectrum that the surface characteristics of the composite oxide support of Example 1 are as follows: -1 There are three characteristic peaks at 2850-2960cm -1 There are three characteristic peaks.

[0108] [Example 2]

[0109] The preparation method of the TiO2-SiO2 composite carrier is the same as that in Example 1, except that 420 mL of a 0.45 mol / L titanium sulfate solution is replaced by 420 mL of a 0.75 mol / L dilute sulfuric acid solution of titanic acid to obtain a TiO2-SiO2 composite carrier with a TiO2 content of 25 wt% (SiO2 content of 75 wt%).

[0110] Take 4g of dimethyldioctadecylammonium chloride, add 96g of o-xylene, mix evenly with 8mL of hydrochloric acid (mass fraction 37wt%), prepare an impregnation solution, use the above impregnation solution to impregnate the TiO2-SiO2 composite carrier at 20°C, impregnate for 2h, and then dry at 60°C for 12h to obtain a TiO2-SiO2 composite oxide carrier.

[0111] The infrared spectrum of the obtained TiO2-SiO2 composite oxide support is similar to that of the composite oxide support in Example 1, and the surface characteristics are as follows: -1 There are three characteristic peaks at 2850-2960cm -1 There are three characteristic peaks.

[0112] [Example 3]

[0113] The preparation method of the TiO2-SiO2 composite carrier is the same as that in Example 1, except that 420 mL of a 0.45 mol / L titanium sulfate solution is replaced by 398 mL of a 0.38 mol / L titanium tetrachloride solution to obtain a TiO2-SiO2 composite carrier with a TiO2 content of 12 wt% (SiO2 content of 88 wt%).

[0114] Take 3g of hexadecyltrimethylammonium chloride, add 97g of o-xylene, mix evenly with 7mL of hydrochloric acid (mass fraction 37wt%), prepare an impregnation solution, use the above impregnation solution to impregnate the TiO2-SiO2 composite carrier at 40°C, impregnate for 2h and then dry at 100°C for 12h to obtain a TiO2-SiO2 composite oxide carrier.

[0115] The infrared spectrum of the obtained TiO2-SiO2 composite oxide support is similar to that of the composite oxide support in Example 1, and the surface characteristics are as follows: -1 There are three characteristic peaks at 2850-2960cm -1 There are three characteristic peaks.

[0116] [Example 4]

[0117] The preparation method of the TiO2-SiO2 composite carrier is the same as that in Example 1, except that 420 mL of a solution of titanium sulfate with a concentration of 0.45 mol / L is replaced by 360 mL of an ethanol solution of tetrabutyl titanate with a concentration of 0.63 mol / L to obtain a TiO2-SiO2 composite carrier with a TiO2 content of 18 wt% (SiO2 content of 82 wt%).

[0118] Take 2g of C 12-14 -alkyl dimethyl ethyl benzyl ammonium chloride, add 98g of o-xylene, mix evenly with 5mL of hydrochloric acid (mass fraction 37wt%), prepare an impregnation solution, use the above impregnation solution to impregnate the TiO2-SiO2 composite oxide support at room temperature, impregnate for 2h and then dry at 60℃ for 12h to obtain a TiO2-SiO2 composite oxide support.

[0119] The infrared spectrum of the obtained TiO2-SiO2 composite oxide support is similar to that of the composite oxide support in Example 1, and the surface characteristics are as follows: -1 There are three characteristic peaks at 2850-2960cm -1 There are three characteristic peaks.

[0120] [Example 5]

[0121] The method of Example 1 was followed, except that titanium sulfate was replaced by zirconium tetrachloride, and a ZrO2-SiO2 composite carrier was finally obtained. A ZrO2-SiO2 composite carrier with a ZrO2 content of 15 wt% (SiO2 content of 85 wt%) was obtained.

[0122] Take 1g of dimethyldioctadecylammonium chloride, add 99g of o-xylene, mix evenly with 3mL of hydrochloric acid (mass fraction 37wt%), prepare an impregnation solution, use the above impregnation solution to impregnate the ZrO2-SiO2 composite carrier at 20°C, impregnate for 2h, and then dry at 60°C for 12h to obtain a ZrO2-SiO2 composite oxide carrier.

[0123] The infrared spectrum of the obtained ZrO2-SiO2 composite oxide support is similar to that of the composite oxide support in Example 1. The surface characteristics are as follows: -1 There are three characteristic peaks at 2850-2960cm -1 There are three characteristic peaks.

[0124] [Example 6]

[0125] Take 85g of SiO2 microsphere carrier, impregnate 280mL of titanium sulfate solution with a concentration of 0.45mol / L at 25℃ for 6h, dry the precipitate at 110℃ for 6h, and calcine at 550℃ for 5h. Then impregnate 300mL of zirconium nitrate solution with a concentration of 0.14mol / L at 25℃ for 4h, dry the precipitate at 110℃ for 8h, and calcine at 550℃ for 6h.

[0126] A TiO2-ZrO2-SiO2 composite carrier (SiO2 content is 85wt%) with a TiO2 content of 10wt% and a ZrO2 content of 5wt% was obtained.

[0127] Take 5g of dimethyldioctadecylammonium chloride, add 95g of o-xylene, mix evenly with 10mL of hydrochloric acid (mass fraction 37wt%), prepare an impregnation solution, use the above impregnation solution to impregnate the TiO2-ZrO2-SiO2 composite carrier at room temperature, impregnate for 2h and then dry at 60℃ for 12h to obtain a TiO2-ZrO2-SiO2 composite oxide carrier.

[0128] The infrared spectrum of the obtained TiO2-ZrO2-SiO2 composite oxide support is similar to that of the composite oxide support in Example 1, and the surface characteristics are as follows: -1 There are three characteristic peaks at 2850-2960cm -1 There are three characteristic peaks.

[0129] [Example 7]

[0130] The preparation method of the TiO2-SiO2 composite oxide carrier is the same as that of Example 1, except that the SiO2 microsphere carrier is replaced by a SiO2 microsphere carrier with a particle size of 10 μm and an average pore size of 200 nm.

[0131] The infrared spectrum of the obtained TiO2-SiO2 composite oxide support is similar to that of the composite oxide support in Example 1, and the surface characteristics are as follows: -1 There are three characteristic peaks at 2850-2960cm -1 There are three characteristic peaks.

[0132] [Example 8]

[0133] The preparation method of the TiO2-SiO2 composite oxide carrier is the same as that in Example 1, except that the SiO2 microsphere carrier is replaced by a SiO2 microsphere carrier with a particle size of 5 μm and an average pore size of 120 nm.

[0134] The infrared spectrum of the obtained TiO2-SiO2 composite oxide support is similar to that of the composite oxide support in Example 1, and the surface characteristics are as follows: -1 There are three characteristic peaks at 2850-2960cm -1 There are three characteristic peaks.

[0135] [Example 9]

[0136] The preparation method of the TiO2-SiO2 composite oxide carrier is the same as that of Example 1, except that the SiO2 microsphere carrier is replaced by a SiO2 microsphere carrier with a particle size of 30 μm and an average pore size of 1000 nm.

[0137] The infrared spectrum of the obtained TiO2-SiO2 composite oxide support is similar to that of the composite oxide support in Example 1, and the surface characteristics are as follows: -1 There are three characteristic peaks at 2850-2960cm -1 There are three characteristic peaks.

[0138] [Example 10]

[0139] 100 g of the TiO2-SiO2 composite oxide carrier prepared in Examples 1-3 was respectively put into 500 mL of palladium chloride solution with a Pd content of 0.2-2.1 g, immersed for 180 minutes, dried at 110° C. for 6 hours, and then calcined at 500° C. for 4 hours to obtain a Pd / TiO2-SiO2 catalyst (heterogeneous catalyst AC) with a Pd content of 0.2-2 wt%. The details are shown in Table 1.

[0140] Heterogeneous catalyst A was subjected to TEM characterization. Figure 2 ,from Figure 2It can be seen that the active component Pd is evenly dispersed, the atomic cluster particle size of the active component is 2 to 5 nm, and the average atomic cluster particle size is 2.7 nm.

[0141] [Example 11]

[0142] 100 g of the TiO2-SiO2 composite oxide carrier prepared in Example 1 and Example 4 were respectively put into 200 mL of an aqueous ammonia solution of ammonium molybdate with a Mo content of 0.10 to 0.51 g, immersed for 120 minutes, dried at 110°C for 6 hours, and then calcined at 500°C for 4 hours to obtain a carrier of Mo-modified SiO2 and TiO2 with a content of 0.1 to 0.5 wt%.

[0143] 100 g of the Mo-modified SiO2 and TiO2 carrier prepared above was put into 500 mL of palladium chloride solution with a Pd content of 0.5-2.1 g, immersed for 180 minutes, dried at 110° C. for 6 hours, and then calcined at 500° C. for 4 hours to obtain a Pd-Mo / TiO2-SiO2 catalyst (heterogeneous catalyst DG) with a Pd content of 0.5-2 wt%. The details are shown in Table 1.

[0144] [Example 12]

[0145] The method of Example 11 was followed, except that the TiO2-SiO2 composite oxide support prepared in Example 1 was replaced by the composite oxide supports prepared in Example 5 and Example 6, respectively, to obtain a heterogeneous catalyst HI). The details are shown in Table 1.

[0146] [Example 13]

[0147] 100 g of the TiO2-SiO2 composite oxide carrier prepared in Example 1 was put into 200 mL of an aqueous ammonia solution of ammonium molybdate with a Mo content of 0.51 g, immersed for 120 minutes, dried at 110°C for 6 hours, and then calcined at 600°C for 5 hours to obtain a 0.5 wt% Mo-modified SiO2 and TiO2 carrier.

[0148] 100 g of the Mo-modified SiO2 and TiO2 carrier prepared above was put into 500 mL of palladium chloride solution with a Pd content of 2.1 g, immersed for 180 minutes, dried at 110° C. for 6 hours, and then calcined at 600° C. for 5 hours to obtain a Pd-Mo / TiO2-SiO2 catalyst (heterogeneous catalyst J) with a Pd content of 2 wt%. The details are shown in Table 1.

[0149] [Example 14]

[0150] 100 g of the TiO2-SiO2 composite oxide carrier prepared in Example 1 was put into 200 mL of an aqueous ammonia solution of ammonium molybdate with a Mo content of 0.51 g, immersed for 120 minutes, dried at 110°C for 6 hours, and then calcined at 650°C for 8 hours to obtain a 0.5 wt% Mo-modified SiO2 and TiO2 carrier.

[0151] 100 g of the Mo-modified SiO2 and TiO2 carrier prepared above was put into 500 mL of palladium chloride solution with a Pd content of 2.1 g, immersed for 180 minutes, dried at 110° C. for 6 hours, and then calcined at 650° C. for 8 hours to obtain a Pd-Mo / TiO2-SiO2 catalyst (heterogeneous catalyst K) with a Pd content of 2 wt%. The details are shown in Table 1.

[0152] [Example 15]

[0153] The method of Example 11 was followed, except that the TiO2-SiO2 composite oxide support prepared in Example 1 was replaced by the composite oxide supports prepared in Examples 7-9, respectively, to obtain heterogeneous catalysts L, M, and N. The details are shown in Table 1.

[0154] Table 1

[0155]

[0156] The particle size, average pore size, and specific surface area of ​​the heterogeneous catalyst AN were tested, and the results are shown in Table 2.

[0157] The particle size was determined according to the NB / SH / T 0951-2017 test method using a laser particle size analyzer model MS2000 produced by Malvern.

[0158] Average pore size and specific surface area The average pore size distribution and porosity of solid materials are determined according to the first part of the mercury injection method of GBT 21650.1-2008 mercury injection method and gas adsorption method, using the AutoPore IV 9500 high-performance automatic mercury injection instrument of Micromeritics Instruments, USA.

[0159] Table 2

[0160]

[0161] [Test Example 1]

[0162] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of heterogeneous catalyst A, 0.4g of homogeneous catalyst triphenylphosphine rhodium chloride, and 1.0g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 6MPa, and reaction time 8h; hydrogenated nitrile rubber is obtained.

[0163] The obtained hydrogenated nitrile rubber was tested for its degree of hydrogenation (unsaturation) using the test method of SH / T1762-2008 / ISO 14558:2000. The result showed that the degree of hydrogenation was 95.7%.

[0164] The obtained hydrogenated nitrile rubber was tested for selectivity by infrared spectrum detection. The instrument used was Nicolet 560 Fourier transform infrared spectrometer produced by Nicolet Company of the United States. It was detected that the absorption peak intensity of -CN in the spectrum did not weaken after hydrogenation, and no absorption peak representing -NH2 appeared, indicating that -CN did not change before and after the reaction, that is, -CN was not hydrogenated, and the selectivity was 100%. The result showed that the selectivity was 100%.

[0165] [Test Example 2]

[0166] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of heterogeneous catalyst A, 0.4g of homogeneous catalyst triphenylphosphine rhodium chloride, and 1.0g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 8MPa, and reaction time 6h; hydrogenated nitrile rubber is obtained.

[0167] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 96.2% and the selectivity was 100%.

[0168] [Test Example 3]

[0169] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of heterogeneous catalyst B, 0.4g of homogeneous catalyst triphenylphosphine rhodium chloride, and 1.0g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 8MPa, and reaction time 6h; hydrogenated nitrile rubber is obtained.

[0170] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 96.0% and the selectivity was 100%.

[0171] [Test Example 4]

[0172] Take 2L of 3wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of heterogeneous catalyst C, 0.5g of homogeneous catalyst triphenylphosphine rhodium chloride, and 1.2g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 8MPa, and reaction time 6h; hydrogenated nitrile rubber is obtained.

[0173] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 95.3% and the selectivity was 100%.

[0174] [Test Example 5]

[0175] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of heterogeneous catalyst D, 0.4g of homogeneous catalyst triphenylphosphine rhodium chloride, and 1.0g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 8MPa, and reaction time 6h; hydrogenated nitrile rubber is obtained.

[0176] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 97.6% and the selectivity was 100%.

[0177] [Test Example 6]

[0178] The heterogeneous catalyst D after the reaction of Test Example 5 was centrifuged and recovered, stirred and washed in an organic solvent chlorobenzene for 4 hours, and centrifuged. The same reaction conditions as Test Example 5 were adopted, and it was added to the reaction system again to investigate its NBR supported catalytic performance. The experiment was repeated for 3 times, and the results of hydrogenation degree (according to the method of Test Example 1) and selectivity (NMR determination: comparing the content of CN groups in the raw material and the hydrogenation product) are listed in Table 3.

[0179] Table 3

[0180] Reuse 1 time Reuse 2 times Reuse 3 times Degree of hydrogenation 93.1% 91.5% 90.4% Selectivity 100% 100% 100%

[0181]

Test Example 7

[0182] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of heterogeneous catalyst E, 0.4g of homogeneous catalyst triphenylphosphine rhodium chloride, and 1.0g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 8MPa, and reaction time 5h; hydrogenated nitrile rubber is obtained.

[0183] The hydrogenated nitrile rubber obtained was tested for its degree of hydrogenation (unsaturation) and selectivity according to the method of Test Example 1, and the results showed that the degree of hydrogenation was 97.3% and the selectivity was 100%.

[0184]

Test Example 8

[0185] The method of Test Example 1 is followed, except that the heterogeneous catalyst A is replaced by the heterogeneous catalyst F, and finally the hydrogenated nitrile rubber is obtained.

[0186] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 97.9% and the selectivity was 100%.

[0187]

Test Example 9

[0188] The method of Test Example 1 is followed, except that the heterogeneous catalyst A is replaced by the heterogeneous catalyst G, and finally the hydrogenated nitrile rubber is obtained.

[0189] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 93.6% and the selectivity was 100%.

[0190] [Test Example 10]

[0191] The method of Test Example 1 is followed, except that the heterogeneous catalyst A is replaced by the heterogeneous catalyst H, and finally the hydrogenated nitrile rubber is obtained.

[0192] The hydrogenated nitrile rubber obtained was tested for its degree of hydrogenation (unsaturation) and selectivity according to the method of Test Example 1. The results showed that the degree of hydrogenation was 93.2% and the selectivity was 100%.

[0193] [Test Example 11]

[0194] The method of Test Example 1 is followed, except that the heterogeneous catalyst A is replaced by the heterogeneous catalyst I, and finally the hydrogenated nitrile rubber is obtained.

[0195] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 98.1% and the selectivity was 100%.

[0196] [Test Example 12]

[0197] The method of Test Example 1 is followed, except that the heterogeneous catalyst A is replaced by the heterogeneous catalyst J, and finally the hydrogenated nitrile rubber is obtained.

[0198] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 98.0% and the selectivity was 100%.

[0199] [Test Example 13]

[0200] The method of Test Example 1 is followed, except that the heterogeneous catalyst A is replaced by the heterogeneous catalyst K, and finally the hydrogenated nitrile rubber is obtained.

[0201] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 98.1% and the selectivity was 100%.

[0202] [Test Example 14]

[0203] The method of Test Example 1 was followed, except that the reaction conditions were: temperature 80° C., hydrogen pressure 6 MPa, and reaction time 8 h.

[0204] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 93.2% and the selectivity was 100%.

[0205] [Test Example 15]

[0206] The method of Test Example 1 was followed, except that the reaction conditions were: temperature 70° C., hydrogen pressure 6 MPa, and reaction time 8 h.

[0207] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 91.3% and the selectivity was 100%.

[0208] [Test Example 16]

[0209] The method of Test Example 1 was followed, except that the reaction conditions were: temperature 60° C., hydrogen pressure 6 MPa, and reaction time 8 h.

[0210] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 89.3% and the selectivity was 100%.

[0211] [Test Example 17]

[0212] The method of Test Example 1 was followed, except that the reaction conditions were: temperature 50° C., hydrogen pressure 6 MPa, and reaction time 8 h.

[0213] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 88.6% and the selectivity was 100%.

[0214] [Test Example 18]

[0215] The method of Test Example 1 is followed, except that the heterogeneous catalyst A is replaced by the heterogeneous catalyst L, and finally the hydrogenated nitrile rubber is obtained.

[0216] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 95.6% and the selectivity was 100%.

[0217] [Test Example 19]

[0218] The method of Test Example 1 is followed, except that the heterogeneous catalyst A is replaced by the heterogeneous catalyst M, and finally the hydrogenated nitrile rubber is obtained.

[0219] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 95.3% and the selectivity was 100%.

[0220] [Test Example 20]

[0221] The method of Test Example 1 is followed, except that the heterogeneous catalyst A is replaced by the heterogeneous catalyst N, and finally the hydrogenated nitrile rubber is obtained.

[0222] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 96.4% and the selectivity was 100%.

[0223] [Test Example 21]

[0224] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of heterogeneous catalyst D, 0.4g of homogeneous catalyst triphenylphosphine rhodium chloride, and 1.2g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 6MPa, and reaction time 8h; hydrogenated nitrile rubber is obtained.

[0225] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 97.7% and the selectivity was 100%.

[0226] [Test Example 22]

[0227] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of heterogeneous catalyst D, 0.4g of homogeneous catalyst triphenylphosphine rhodium chloride, and 1.6g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 6MPa, and reaction time 8h; hydrogenated nitrile rubber is obtained.

[0228] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 97.8% and the selectivity was 100%.

[0229] [Test Example 23]

[0230] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of heterogeneous catalyst D, 0.4g of homogeneous catalyst triphenylphosphine rhodium chloride, and 2g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 6MPa, and reaction time 8h; hydrogenated nitrile rubber is obtained.

[0231] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 97.7% and the selectivity was 100%.

[0232]

Test Example 24

[0233] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 12g of heterogeneous catalyst D, 0.4g of homogeneous catalyst triphenylphosphine rhodium chloride, and 1.6g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 6MPa, and reaction time 8h; hydrogenated nitrile rubber is obtained.

[0234] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 99.1% and the selectivity was 100%.

[0235] [Test Example 25]

[0236] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of heterogeneous catalyst A, 0.5g of homogeneous catalyst triphenylphosphine ruthenium chloride, and 1.2g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 6MPa, and reaction time 8h; hydrogenated nitrile rubber is obtained.

[0237] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 95.1% and the selectivity was 100%.

[0238] [Test Example 26]

[0239] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of supported catalyst D, 0.08g of homogeneous catalyst triphenylphosphine rhodium chloride, and 0.40g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 95°C, hydrogen pressure 8MPa, and reaction time 8h; hydrogenated nitrile rubber is obtained.

[0240] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 91.5% and the selectivity was 100%.

[0241] [Test comparison example 1]

[0242] The TiO2-SiO2 composite oxide carrier without surface treatment in Example 1 was used, and the infrared spectrum was as follows: Figure 3 As shown, that is, the infrared spectrum of the TiO2-SiO2 composite carrier without surface treatment.

[0243] Then, the active components were loaded according to the method of Example 10, and finally a Pd / TiO2-SiO2 catalyst with a Pd content of 2 wt% was prepared.

[0244] According to the method of Test Example 1, hydrogenated nitrile rubber was finally obtained.

[0245] The hydrogenated nitrile rubber obtained was tested for its degree of hydrogenation (unsaturation) and selectivity according to the method of Test Example 1, and the results showed that the degree of hydrogenation was 86.8% and the selectivity was 99%.

[0246] [Test comparison example 2]

[0247] The TiO2-SiO2 composite oxide carrier of Example 1 was used, and the method of Example 8 was followed, except that Pd was replaced by Rh, to finally obtain a Rh / ZrO2-SiO2 catalyst (heterogeneous catalyst DB1) with a Rh content of 2 wt%.

[0248] The method of Test Example 1 is followed, except that the heterogeneous catalyst A is replaced by the heterogeneous catalyst DB1, and finally hydrogenated nitrile rubber is obtained.

[0249] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 93.1% and the selectivity was 100%.

[0250] [Test comparison example 3]

[0251] The method of Test Example 5 is followed, except that only the heterogeneous catalyst D is used, as follows:

[0252] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 9.4g of heterogeneous catalyst D, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 8MPa, reaction time 6h; hydrogenated nitrile rubber is obtained.

[0253] The hydrogenation degree (unsaturation) and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 58% and the selectivity was 100%.

[0254] [Test comparison example 4]

[0255] The method of Test Example 1 is followed, except that only a homogeneous catalyst is used, as follows:

[0256] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), 0.4g of homogeneous catalyst triphenylphosphine rhodium chloride, and 1.0g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 8MPa, and reaction time 6h; hydrogenated nitrile rubber is obtained.

[0257] The hydrogenated nitrile rubber obtained was tested for its degree of hydrogenation (unsaturation) and selectivity according to the method of Test Example 1, and the results showed that the degree of hydrogenation was 67.2% and the selectivity was 100%.

[0258] [Test comparison example 5]

[0259] Take 85 g of SiO2 microsphere carrier (particle size: 20 μm, average pore size: 110 nm).

[0260] Take 5g of dimethyldioctadecylammonium chloride, add 95g of o-xylene, mix evenly with 10mL of hydrochloric acid (mass fraction 37wt%), prepare an impregnation solution, use the above impregnation solution to impregnate the SiO2 microsphere carrier at 20°C, impregnate for 2h, and then dry at 60°C for 12h.

[0261] The infrared spectrum of the SiO2 carrier after surface treatment is shown in Figure 4 shown.

[0262] It can be seen from Test Examples 1-26 and Comparative Test Examples 1-4 that the present invention adopts a method of coordinating with a homogeneous catalyst to hydrogenate and saturate the polymer material at a relatively low temperature and pressure. The obtained hydrogenated nitrile rubber product has a relatively high degree of hydrogenation and can also ensure the multiple use of the heterogeneous catalyst, and the catalyst is easy to separate and recover.

[0263] pass Figure 1 , Figure 3 to Figure 5 It can be seen that the surface of the composite oxide support is treated with an impregnation solution containing an organic cationic quaternary ammonium salt, and the surface characteristics of the surface-treated composite oxide support are as follows: -1 There are three characteristic peaks at 2850-2960cm -1There are three characteristic peaks at 620-710cm. The infrared spectrum of the TiO2-SiO2 composite oxide carrier without surface treatment and the infrared spectrum of the SiO2 carrier with surface treatment are -1 There are no three characteristic peaks at 2850-2960cm -1 The composite oxide carrier of the present invention can significantly improve the dispersion of active components on the catalyst surface, control the atomic cluster of active components to be no larger than 5nm, and thus significantly improve the hydrogenation activity of the catalyst.

[0264] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this field, under the technical enlightenment provided by the present invention, as common knowledge in the field, other equivalent variations and improvements can also be made, which should also be regarded as the protection scope of the present invention.

Claims

1. A heterogeneous catalyst comprising: A composite oxide carrier of SiO2 and Group IVB metal oxide, and an active component Pd and its oxide loaded on the composite oxide carrier, wherein the Group IVB metal oxide is TiO2 and / or ZrO2; the surface characteristics of the composite oxide carrier are infrared spectrum at 620-710cm -1 There are three characteristic peaks at 2850-2960cm -1 There are three characteristic peaks.

2. The heterogeneous catalyst according to claim 1, characterized in that The composite oxide carrier is obtained by surface treating a composite carrier of SiO2 and Group IVB metal oxide with an impregnation solution containing an organic cationic quaternary ammonium salt; preferably, the organic cationic quaternary ammonium salt is a C6 or higher long-chain alkyl quaternary ammonium salt, more preferably selected from dimethyl dioctadecyl ammonium chloride, hexadecyl trimethyl ammonium chloride and C 12-14 -At least one of alkyl dimethyl ethyl benzyl ammonium chloride.

3. The heterogeneous catalyst according to claim 1, characterized in that Based on the total weight of the composite oxide carrier, the content of Group IVB metal oxide is 5-25wt%, and the content of SiO2 is 75-95wt%; based on the total weight of the heterogeneous catalyst, the content of Pd and its oxide as Pd is 0.5-2wt%.

4. The heterogeneous catalyst according to any one of claims 1 to 3, characterized in that The heterogeneous catalyst further comprises Mo and its oxide supported on the carrier; preferably, the content of Mo and its oxide calculated as Mo is 0.1 to 0.5 wt% based on the total weight of the heterogeneous catalyst; Preferably, the heterogeneous catalyst has a particle size of 5 to 30 μm, an average pore size of 100 to 1200 nm, and a specific surface area of ​​30 to 200 m 2 / g; and / or, the atomic cluster particle size of the active component Pd is not greater than 5nm, preferably 2 to 5nm.

5. A method for preparing a heterogeneous catalyst, comprising the following steps: (1) performing a first impregnation of a SiO2 microsphere carrier with a solution containing a Group IVB metal compound, followed by a first drying and a first calcination to obtain a composite carrier, wherein the Group IVB metal compound is a titanium-containing compound and / or a zirconium-containing compound; (2) treating the surface of the composite support with an impregnation solution containing an organic cationic quaternary ammonium salt to obtain a composite oxide support; (3) The composite oxide support is impregnated with a soluble salt of Pd for a second time, and then dried and calcined for a second time.

6. The preparation method according to claim 5, characterized in that: The impregnation solution containing organic cationic quaternary ammonium salt comprises organic cationic quaternary ammonium salt, solvent and acid; Preferably, in the impregnation solution containing the organic cationic quaternary ammonium salt, the concentration of the quaternary ammonium salt solution is 0.1-10 wt %.

7. The preparation method according to claim 5 or 6, characterized in that: The surface treatment is immersion and drying. Preferably, the immersion conditions include: temperature of 20-60° C., time of 0.5-8 h; the drying conditions include: temperature of 50-120° C., time of 2-10 h.

8. The preparation method according to claim 5, characterized in that: After step (2) and before step (3), the preparation method further comprises: dissolving a soluble salt of molybdenum and impregnating the surface-treated composite oxide support to obtain a Mo-modified surface-treated composite oxide support; Preferably, the soluble salt of Mo is selected from at least one of molybdenum trioxide, ammonium molybdate and ammonium polymolybdate; Preferably, the molar ratio of the soluble salt of molybdenum to SiO2 is 1:1500-2000; Preferably, the solution used for dissolving is selected from at least one of aqueous ammonia, dilute acid solution and alkaline solution.

9. The preparation method according to claim 5, characterized in that: The SiO2 microsphere carrier has a particle size of 5 to 30 μm, and / or an average pore size of 100 to 1200 nm; and / or a specific surface area of ​​30 to 100 m 2 / g; and / or, the titanium-containing compound is at least one selected from titanium sulfate, metatitanic acid, titanium tetrachloride and tetrabutyl titanate; and / or, the zirconium-containing compound is at least one selected from zirconium tetrachloride, zirconium sulfate, zirconium nitrate, zirconium oxychloride and zirconium oxalate; And / or, the organic cationic quaternary ammonium salt is a C6 or higher long-chain alkyl quaternary ammonium salt, more preferably selected from dimethyl dioctadecyl ammonium chloride, hexadecyl trimethyl ammonium chloride and C 12-14 -At least one of alkyl dimethyl ethyl benzyl ammonium chloride; And / or, the soluble salt of Pd is selected from sulfates, nitrates and halides of palladium, preferably at least one of palladium chloride, palladium nitrate, palladium acetate and palladium sulfate.

10. The preparation method according to claim 5, characterized in that: The weight ratio of the SiO2 microsphere carrier to the titanium-containing compound and / or the zirconium-containing compound is 7 to 20:

1.

11. The preparation method according to claim 5, characterized in that: The molar ratio of the composite oxide support to the soluble salt of Pd is 1:150-700.

12. The preparation method according to claim 5, characterized in that: The conditions of the first impregnation include: a temperature of 20-60°C and a time of 0.5-8h; and / or, the conditions of the second impregnation include: a temperature of 20-60°C and a time of 0.5-8h; and / or, the conditions of the first drying include: a temperature of 105-130°C and a time of 2-8h; and / or, the conditions of the second drying include: a temperature of 105-180°C and a time of 2-8h; and / or, the conditions of the first calcination include: a temperature of 450-650°C and a time of 3-8h; and / or, the conditions of the second calcination include: a temperature of 450-650°C and a time of 3-8h.

13. A heterogeneous catalyst obtained according to the preparation method described in any one of claims 5 to 12.

14. A catalyst composition comprising a homogeneous catalyst and the supported catalyst according to any one of claims 1 to 4 and 13.

15. The catalyst composition according to claim 14, characterized in that The homogeneous catalyst includes triphenylphosphine and triphenylphosphine chloride of a platinum group metal; Preferably, the triphenylphosphine chloride of the platinum group metal is triphenylphosphine rhodium chloride and / or triphenylphosphine ruthenium chloride; Preferably, the weight ratio of triphenylphosphine to triphenylphosphine chloride of a platinum group metal is 2 to 5:

1.

16. The catalyst composition according to claim 14 or 15, characterized in that The weight ratio of the supported catalyst to the homogeneous catalyst is 1:0.01-0.

3.

17. A method for hydrogenating a hydrogenated high molecular polymer, comprising: An organic solvent is used to dissolve the high molecular weight polymer, and then the catalyst composition according to any one of claims 14 to 16 is added to carry out the reaction.

18. The preparation method according to claim 17, characterized in that: The high molecular polymer is nitrile rubber.

19. The preparation method according to claim 17, characterized in that: The organic solvent is selected from at least one of chlorobenzene, acetone, butanone, tetrahydrofuran, dichloromethane, chloroform, cyclohexanone, ethyl acetate and dimethylformamide.

20. The preparation method according to any one of claims 17 to 19, characterized in that: The heterogeneous catalyst is used in an amount of 5 to 20 wt% of the high molecular weight polymer; And / or, the reaction conditions include: temperature of 30-90° C., hydrogen pressure of 5-10 MPa, and reaction time of 5-10 h.

21. The hydrogenated high molecular polymer obtained by the preparation method according to any one of claims 17 to 20, preferably, the hydrogenated high molecular polymer is hydrogenated nitrile rubber.

22. Use of the heterogeneous catalyst according to any one of claims 1-4 and 13, the preparation method according to any one of claims 5-12, the catalyst composition according to any one of claims 14-16, the hydrogenation method of the hydrogenated high molecular weight polymer according to any one of claims 17-20, or the hydrogenated high molecular weight polymer according to claim 21 in rubber products, especially in the field of hydrogenated nitrile rubber products.

Citation Information

Patent Citations

  • ZrO2-SiO2 compound oxides, its preparation method and application

    CN101007268A

  • Aluminum zirconium titanium composite oxides carrier and hydrofinishing sulfur-removal arene-removal catalyste

    CN101357342A

  • Preparation of silane coupling agent-modified SiO2 loaded rhodium catalyst and selective hydrogenation application of catalyst to butadiene-acrylonitrile rubber

    CN103537304A

  • Hydrogenated butadiene-acrylonitrile rubber preparation method

    CN104140479A

  • Nitrile rubber selective heterogeneous hydrogenation catalyst and preparation method and hydrogenation method thereof

    CN106268735A